The Patience of Paul - Henley, John (Toronto journal of theology, 2002)
In recent years, we have witnessed an increasing emphasis on the importance of community in certain theological circles beyond, though still including, the Roman Catholic. It is hardly surprising, therefore, that less is being heard of Bultmann-like depictions of the Christian life according to Paul. It seems to me, however—indeed, it has long seemed to me —that there are elements in the thought of the apostle which invite us to beware of those who enthuse too much about the communal dimension of Christian living. Bultmann and many others may have neglected this communal dimension but they were not wrong to draw attention to the room Paul makes for the individual. For the apostle found limits to the achievement of Christian community and so, in the rest of this salute to a friend shaped by Scottish Presbyterianism, I shall focus on three aspects of Paul's teaching about life in the body of Christ and also say something about their continuing relevance.